SOS - an android application for emergencies - Suryawanshi, Akash (Kansas State University, 2014)
Master of Science === Department of Computing and Information Sciences === Daniel A. Andresen === The aim of the project is to develop an Android application that lets its users to send notifications in case of an emergency or a panic situation. The users can send multiple text messages and emails on the press of a single button. The phone numbers, email ids and the contents of the text and email messages can be set from within the application. The text messages and emails sent, along with the content, also have the last known location of the user. This is very helpful in tracking the whereabouts of the person. The user can also call 911 directly from within the application, if the nature of the situation demands it. Additionally the user of the application may allow the app to track their location. If this option is selected, the application fetches the device’s location at about every 15 minutes and stores it in a database. This information is very useful and can be used in a variety of ways. One such use of the location data is from within the Android app where the user can view a map that shows their location history over a period of time for a particular day.